Segmentally aware: know when to merge and when to purge - Ma, Yao; Xu, Jiahua (My University, 2019)
Purpose The purpose of this paper is to hone in on the degree of segment-level integration relative to corporate post-merger performance. Design/methodology/approach The sample consists of 89 segments in 29 combined companies resulting from large mergers and acquisitions (M&A) transactions between 2001 and 2014 in the pharmaceutical and chemical industries worldwide. The authors track the change through M&A in performance of segments with different integration forms as well as performance of entire companies with different integration levels. Findings The authors find that integrating the segments from the target significantly improves the acquirer’s overall performance, as well as the concerned segments’ performance, following an M&A transaction. Whereas the segments from the target company, when left unintegrated, not only exhibit subpar performance among all the segments, but also appear responsible for the worsening corporate performance. Various possible reasons for this contrast are discussed. Originality/value This paper raises awareness of the significance of segment-level analyses, and contributes to the post-merger integration (PMI) research by examining the influence of structural integration on operating segments. To the best of our knowledge, this paper is the first to investigate integration forms and the post-merger financial performance of various segments within companies.
Keywords: Mergers and acquisitions; Post-merger integration; Operating segment; Post-merger performance; Segment performance